Model Problem-Based Learning (PBL) dengan Strategi Pembelajaran Berdiferensiasi untuk Meningkatkan Motivasi Belajar dan Hasil Belajar Kognitif: PROBLEM-BASED LEARNING (PBL) MODEL WITH DIFFERENTIATION LEARNING STRATEGIES TO IMPROVE LEARNING MOTIVATION AND COGNITIVE LEARNING OUTCOMES - Kusumawati, Retno Indah; Fitrihidajati, Herlina; Triwahyudi, Hery (Universitas Muhammadiyah Surabaya, 2024)
The objectives of this study include three things, namely (1) to describe the implementation of the PbL model with differentiated learning strategies to increase learning motivation and cognitive learning outcomes; (2) Describe students' learning motivation after implementing the PbL model with a differentiated learning strategy; and (3) describe the increase in students' cognitive learning outcomes after implementing the PbL model with a differentiated learning strategy. The method used was classroom action research (CAR) with class X students as research subjects. Data were collected using observation techniques, questionnaires, and tests, with each instrument being an observation sheet on the application of the PBL model with differentiated learning strategies, learning motivation questionnaire sheets, and study result test sheet. Based on the research that has been done, it is concluded that (1) the application of the PbL model with a differentiated learning strategy is said to be successful if it reaches a percentage of ≥ 80%; (2) classical student learning motivation is said to be achieved if the percentage of learning motivation of all students in the class reaches ≥ 80%; (3) Students are said to have completed learning individually if they get a score of ≥ 75. Meanwhile, classical completeness is said to have been achieved if all students in the class have completed their studies with a percentage of ≥ 80%.